Geometric modeling of contours of cuts of canal surfaces of air intakes of air drives oriented on machine algorithms - Ходак, М. О.; Ситниченко, В. В. (Proceedings of National Aviation University (archive), 2000)
Considered is the application of machine algorithms at some separate stages of geometric modeling of internal contours of characteristic cuts of canal surfaces of air intakes of air gas turbine drives